Assessment of torque performance during screwing in beech plywood reinforced with glass fiber in phenol-formaldehyde resin - Kayacık, Gökhan; Tor, Önder (BioResources, 2025)
This study aimed to develop plywood, which is generally used as a building material in outdoor areas, by adding low-cost glass fiber and to examine some physical and mechanical properties of the developed plywood. For this, beech veneers (600 × 600 mm dimension, 2 mm thickness in 3% to 5% humidity) were glued with phenol-formaldehyde adhesive at the levels of 10%, 20%, and 30% by adding powdered e-type glass fiber in two different sizes (25 µm and 10 µm) to produce seven-layer beech plywood. Density, equilibrium moisture content, thickness swelling, tensile-shearing, and tensile-perpendicular to the surface were evaluated on test samples cut from the beech plywood in 50 × 50 mm dimension, and screwing torque values were carried out on test samples cut in 500 × 50 mm dimensions. Two-factor analysis of variance (ANOVA) was performed separately for the tests above. Results indicated that in cases where interactions between the glass fiber size and ratio were significant at the 0.05 significance level, the least significant difference value (LSD) analysis of the interaction was performed. According to LSD results, the tensile strength perpendicular to the surface decreased as the glass fiber ratio was increased.
Keywords: maximum torque; seating torque; screw; tensile resistance; tensile-shear resistance; perpendicular to the surface; TP248.13-248.65; Biotechnology